2020
DOI: 10.1021/acscatal.0c02222
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Engagement and Catalytic Mechanisms of N-Acetylglucosaminyltransferase V

Abstract: α-Mannoside β-1,6-N-acetylglucos­aminyl­transferase V (MGAT5) is a mammalian glycosyltransferase involved in complex N-glycan formation, which strongly drives cancer when overexpressed. Despite intense interest, the catalytic mechanism of MGAT5 is not known in detail, precluding therapeutic exploitation. We solved structures of MGAT5 complexed to glycosyl donor and acceptor ligands, revealing an unforeseen role for donor-induced loop rearrangements in controlling acceptor substrate engagement. QM/MM metadynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…This is consistent with previous study in which GnT-V mutants lacking a part of the N domain fully retained their activity toward oligosaccharides ( 27 ). In addition, a soluble GnT-V catalytic domain that lacks the whole N domain and was used for structural studies is still active toward oligosaccharides ( 20 , 21 ). These data demonstrated that the N domain is not involved in a monosaccharide transfer reaction itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with previous study in which GnT-V mutants lacking a part of the N domain fully retained their activity toward oligosaccharides ( 27 ). In addition, a soluble GnT-V catalytic domain that lacks the whole N domain and was used for structural studies is still active toward oligosaccharides ( 20 , 21 ). These data demonstrated that the N domain is not involved in a monosaccharide transfer reaction itself.…”
Section: Discussionmentioning
confidence: 99%
“…The other possibility is that the N domain could change the conformation of the catalytic domain by moving like a pendulum. As the N domain is connected to the neighboring domain via two highly flexible loops ( 19 , 21 ), movement of the N domain might alter the conformation of the catalytic region for efficient product release. However, if this putative conformational change induced by the N domain is a prerequisite for GnT-V action, GnT-VΔN would lose activity regardless of the type of substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The raised level of GlcNAc-branching N-glycans is a result of increased activity of mannoside N-acetylglucosaminyltransferase 5 (GnT-V), which is encoded by the MGAT5 gene, often activated in cancer cells [59]. Activity of GnT-V leads to the formation of complexed tri-and tetra-antennary structures (Figure 1A), which can affect the stability, functional activity and half-life of proteins, as well as membrane dynamics [61,103]. Furthermore, branched N-glycans can be modified via β1,4-galactosyltransferases (β1,4-GalTs), thus elongated with poly-N-acetyllactosamine repeats, and finally capped with sialic acid or fucose.…”
Section: Branched N-glycansmentioning
confidence: 99%
“…Another interesting study was recently reported by Darby et al, who analyzed the α‐mannoside β‐1,6‐ N ‐acetylglucosaminyltransferase V (MGAT5), which is a mammalian glycosyltransferase contributing to N ‐glycan formation. MGAT5 is known to strongly drive cancer when overexpressed 101 . The catalytic mechanism of MGAT5 was unknown, precluding therapeutic exploitation.…”
Section: Computational Chemistry Toolsmentioning
confidence: 99%